Composite functional metasurfaces for multispectral achromatic optics - Ori Avayu (Nature Portfolio, 2017)
Metasurfaces promise the possibility of thin optical elements, like lenses, but these mostly suffer from chromatic aberrations. Here, the authors demonstrate a multilayer fabrication approach with multiple materials to realise achromatic lenses and multispectral functional optical elements.